Effect Of Weedy Rice (Oryza sativa L.) On The Yield Of Cultivated Rice (Oryza sativa L.) In Greenhouse And Field Environment - Salmah, Tajuddin (2014)

(untitled)
This study aimed to investigate the competitive abilities of cultivated rice (CR) and weedy rice (WR). This study was performed over a period of twelve months from January 2012 to December 2012 in greenhouse and field environments. Kajian ini bertujuan untuk mengkaji keupayaan persaingan padi sawah (CR) terhadap padi angin (WR). Kajian ini yang telah dijalankan selama dua belas bulan dari Januari 2012 hingga Disember 2012 di persekitaran rumah hijau dan lapangan.